"Cultures of populism: institutions and hegemonic practices" – a brief introduction. Issue 3 (2nd July 2020) - Williams, Merle A.
ABSTRACT: This short Introduction sets the context for the nine articles included in Safundi's special issue on "Cultures of Populism: Institutions and Hegemonic Practices" (Vol. 21, no. 3) by establishing connections with the colloquium of the same name that was hosted at the University of the Witwatersrand in Johannesburg from 10th until 13th July 2019. At the conference, populism (whether of the political right or the left) was examined in relation to democracy, the role of elites, and possible futures for the Humanities. Drawing on a range of theoretical perspectives, papers considered the diverse histories of populism, as well as varied occurrences of this phenomenon across the globe.